Occupier satisfaction and its impact on investment returns from UK commercial real estate. Issue 2 (6th March 2017) - Sanderson, Danielle Claire; Devaney, Steven
Abstract : Purpose: The purpose of this paper is to investigate the relationship between occupiers' satisfaction with the property management service they receive and the financial performance of commercial real estate. Design/methodology/approach: The study uses occupier satisfaction data for 240 UK commercial properties collected over a 12-year period and the annual total returns achieved by those properties. Various statistical techniques are employed to assess whether increasing occupier satisfaction leads to greater returns for investors. These include comparing excess returns and risk-adjusted returns with occupier satisfaction at each property to assess whether superior property management generates outperformance ("positive alpha"). The study also investigates whether the relationship between occupier satisfaction and returns is the same across all sectors and whether it is affected by market conditions. Findings: A positive correspondence is found between benchmark outperformance and occupier satisfaction. The relationship is similar for all sectors of commercial property and is particularly strong during the Global Financial Crisis, indicating that paying attention to satisfying the needs of occupiers has particular benefits during periods when the supply of commercial real estate exceeds demand. Research limitations/implications: The sample of properties was restricted to those for which occupier satisfaction data had been collected by RealService Ltd and whose owners permitted access to the financial performance results. This meant that the properties belong to only three landlords, all UK REITs that care sufficiently about occupier satisfaction to commission studies. Thus the findings might not apply to all commercial properties. The mechanism by which the positive relationship between satisfaction and financial performance occurs is not tested, but the conventional mechanisms of reputation and customer loyalty (the "service-profit chain") are discussed. Practical implications: The findings suggest that it is worthwhile for landlords, or property managers acting on their behalf, to understand the needs of their occupiers in order to deliver the level of service that those occupiers desire. Leases in the UK are generally "triple net" and the total returns used for this analysis are net of property management costs, so the positive relationship between satisfaction and performance is not the result of economising on service delivery. A further implication is that valuers should take more account of occupier satisfaction when assessing the capital value of a property, from which total returns are assessed. Originality/value: Demonstrating the links between customer service, customer satisfaction and business profitability is rarely attempted because of the many confounding factors that affect profitability. UK listed real estate companies are typically reluctant to reveal the financial performance of individual properties, and information about occupiers' satisfaction is not generally available. The authors were fortunate to be granted access to a time series of such data, and to be able to demonstrate that attention to delivering a property management service that satisfies occupiers is likely to bring financial rewards to the owners of the property.